Supply Chain Management (SCM), Environmental Factors and Porter Five Forces: A Case Study of Malaysia Airlines Berhad (MAB) - Mandy Mok Kim Man (International Journal of Supply Chain Management, 2016)
Abstract This paper examines the supply chain management (SCM) concept and Porter Five Forces which practiced by the Malaysia Airlines Berhad (MAB). Besides that, contingency factors, such as environmental uncertainty and intensity of competition were reviewed to provide an insight study about the environmental influences on the strategies implemented in MAB. Using case study of MAB, this paper highlights that supply chain management need to take into account environmental uncertainty and competition factors to increase the service value in supply chain. Overall, this paper emphasized that SCM and strategies suit with environmental change are necessary to be practiced in organization for future planning and development of the organization.